CFD analysis of 500W centrifugal compressor performance / M. Z. Azmizam and A. M. I. Mamat - Azmizam, M. Z.; Mamat, A. M. I. (Smart Manufacturing Research Institute (SMRI), 2024)
This paper used Computational Fluid Dynamics (CFD) to analyse the performance of a 500W centrifugal compressor, aiming to develop a comprehensive performance map under various operating conditions. The methodology includes stages such as geometry and grid generation, mesh generation, boundary condition setup, and CFD analysis using ANSYS software. The compressor blade profile was generated using ANSYS BladeGen, followed by meshing that consists of roughly 446,886 nodes and 417,312 elements via ANSYS TurboGrid. Boundary conditions were established by using the CFX-Pre, detailing the inlet and outlet conditions, such as mass flow rate, total temperature, and total pressure. The CFD simulations were conducted using CFX-Solver for 500 iterations, targeting a residual mean square (RMS) of 1 × 10-5, and the results were analysed using CFXPost. The analysis was conducted under ambient conditions with a mass flow rate ranging from 0.01 kg/s to 0.065 kg/s and speeds of 60,000 rpm, 70,000 rpm, and 80,000 rpm. The expected outcomes include detailed performance maps that provide valuable insights into parameters like Mass Flow Parameter (MFP), Pressure Ratio (PR), and Efficiency (η) across different operating conditions. By employing the k-ε turbulence model in ANSYS CFX, the project aims to offer significant insights into the compressor's performance characteristics. The analysis, conducted under ambient conditions with a mass flow rate ranging from 0.01 kg/s to 0.065 kg/s and speeds of 60,000 rpm, 70,000 rpm, and 80,000 rpm, yielded significant results. The maximum power achieved at the design speed was 771 W at a mass flow rate of 0.05 kg/s. The maximum efficiency recorded was 77.8% at the same mass flow rate, with the efficiency average around 65.5% across the design speed.